Lentivirus vectors construction of SiRNA targeting interference GPC3 gene and its biological effects on liver cancer cell lines Huh-7 - Lei, Chang-Jiang; Yao, Chun; Pan, Qing-Yun; Long, Hao-Cheng; Li, Lei; Zheng, Shu-Ping; Zeng, Cheng; Huang, Jian-Bin (Asian Pacific journal of tropical medicine, 2014)
Objective:To build GPC3 gene short hairpin interference RNA（shRNA）slow virus veclor.observe expression of Huh-7 GPC3 gene in human liver cell line proliferation apoptosis and the effect of GPC3 gene influencing on liver cancer cell growth,and provide theoretical basis for genc therapy of liver cancer.Methods:Hepatocellular carcinoma cell line Huh-7 wsa transfected by a RNA interference technique.GPC3 gene expression in a variety of liver cancer cell lines was detected by fluorescence quantitative PCR.Targeted GPC3 gene seqnences of small interfering RNA（siRNA）PGC-shRNA-GPC3 were restructured.Stable expression cell linse of siRNA were screened and established with the heplp of liposomes(lipofectamineTM2000)as carrier transfcetion of human liver cell lines.In order to validate siRNA interference efficiency.GPC3 siRNA mRNA expression was detected after transfection by using RT-PCR and Western blot.The absorbance value of the cells of blank group,untransfection group and transfection group,the cell cycle and cell apoptosis were calculated,and effects of GPC3 gene nn Huh-7 cell proliferation and apoptosis were observed.Results:In the liver cancer cell lines Huh-7 GPC3 gene showed high expression.PGC-shRNA-GPC3 recombinant plasmid was constructde successfully via sequencing validation.Stable recombinant plasmid transfected into liver cancer cell linse Huh-7can obviously inhibit GPC3 mRNA expression level.Conclusions:The targeted GPC3 siRNA can effectively inhibit the expression of GPC3.